Analysis of COMPASS, a New Comprehensive Plasmid Database Revealed Prevalence of Multireplicon and Extensive Diversity of IncF Plasmids - Douarre, Pierre-Emmanuel; Mallet, Ludovic; Radomski, Nicolas; Felten, Arnaud; Mistou, Michel-Yves (Frontiers in Microbiology, 2020)
Plasmids are genetic elements that enable rapid adaptation and evolution by transferring genes conferring selective advantages to their hosts. Conjugative plasmids are predominantly responsible for the ever-so-growing global dissemination of antimicrobial resistance, representing an important threat to global health. As the number of plasmid sequences grows exponentially, it becomes critical to depict the global diversity and decipher the distribution of circulating plasmids in the bacterial community. To this end, we created COMPASS, a novel and comprehensive database compiling 12 084 complete plasmids with associated metadata from 1 571 distinct species isolated worldwide over more than 100 years. The curation of the database allowed us to identify identical plasmids shared between different species revealing their disseminating potential and stability. We outlined and analyzed all relevant features, plasmid properties, host range and characterized their replication and mobilization systems using MOB-suite. The analysis revealed that the current knowledge embedded in the current typing schemes fail to classify all the plasmid sequences collected in COMPASS. We were able to categorize 6 828 and 5 229 plasmids by replicon and MOB typing, mostly associated to Proteobacteria and Firmicutes. We then searched for the presence of multiple core genes involved in replication and propagation. Our results showed that 2 403 plasmids carried multiple replicons that were distributed in 206 bacterial species. The co-integration of replicon types from different Inc groups is an adaptive mechanism, which plays an important role in plasmid survival and dissemination by extending their host range. Our results highlight the crucial role of IncF alleles (present in 56% of all multireplicons) and revealed that IncH, IncR and IncU replicons were also frequently encoded in multireplicons. Here, we provided a comprehensive picture of the different IncF subtypes by identifying 20 different profiles in 849 IncF multireplicons, which were mostly associated with Enterobacteriaceae. These results form the basis for a novel IncF plasmid nomenclature based on different allelic profiles.